Seminar Inovasi Pembelajaran Berbasis Tematik - Baidowi, Ach.; Abdussalam, Abdussalam (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2023)
Thematic learning becomes very important in the era of the 2013 curriculum and also the current independent learning curriculum, the output of the two curricula is strengthening the processes and learning outcomes for students. The seminar was conducted with the aim of strengthening and increasing the teacher's pegagogical competence, especially in terms of learning innovation. The seminar was conducted offline with a duration of 200 minutes on August 29 2022 at UPTD SDN Pangilen 3 Sampang which was attended by 8 teachers. The speaker uses the help of a laptop as a medium for delivering material. The results of the seminar implementation: 1) The first speaker gave material about holistic and meaningful learning, the second speaker gave authentic and active learning material. 2) The seminar runs actively as evidenced by lively discussions. 3) The results of the teacher's seminar increasingly understand and can practice holistic, meaningful, authentic and active learning in front of the presenters. The impact of this seminar is as a reference material and study for other schools, especially rural schools that have not implemented thematic learning as a whole.